The impact of material incentives on the motivation of insurance company officers: A developmental perspective - Balachandar, G.; Panchanatham, N.; Subramanian, K. (Institute for Management and Business Research (IMBRe), Universiti Utara Malaysia, 2011)
Findings show that nearly 80% of the Indian population is without life insurances in a society with a weak social security and a pension system that hardly can provide for an old age income security.Lately, insurance companies, by tapping into urban, semi-urban and rural areas far and near mainly through innovative insurance plans, novel marketing techniques, and new distribution channels, have managed to get a great majority of the population of low and middle income groups alike to be attracted to insurance.The efforts of the officers of these insurance companies, both physically and mentally, coupled with apt administration and able leadership capacities have led to the expansion of the business of the insurance companies.However, these insurance officers have to be motivated to involve themselves in their duties continuously without frustration.Considering the importance of motivation on insurance officials, this study is an attempt to mark out the relationship between the material incentives (Pay, Flexible working hours, Promotion and Benefits) and motivation. Based on a sample of 80 insurance company officers in Tamilnadu, India, the data was analyzed using statistical tools such as Z-test, correlation analysis, and regression analysis and the results show the impact of material incentives on the motivations of the officers of insurance companies.